Working Group to Study the System of Satisfactorily Organising Supplies, Services and Works in the North Easter Region - Planning Commission (Planning Commission, 1985)
The development of North Eastern region needs a special strategy end approach because of its geographical, social and cultural isolation and of distinct traditions of the hills and tribal areas. Based on the impressions of the Member Secretary, Planning Commission during his tour to the North Eastern region and the observations of the other Officers of the Planning Commission a paper on ’’strategies on development in the North East - a fresh look” was prepared and discussed in the meeting of Secretaries held on 13th September, 1982, under the Chairmanship of Shri C.R. Krishna Swami Rao Saheb, Cabinet Secretary. The Committee, recognising the fact that the matter of organising supplies and works in the region arc not satisfactory mainly due to in-adequate infrastructure and dependency of the region on contractors mainly from outside, recommended that a Working Group to review the current status of the problem and to evolve the concrete programme of action may be set up for the system of organising supplies, services and works in the region. In pursuance of this recommendation Planning Commission vide their Oil Number PC(P)8(2)/NEC/82- MLP-(3) dt. 29th January 1983 set up a Working Group.to study the system of satisfactorily organising supplies, services and works in the north eastern region. The composition of the give-up is given below
Planinng Commission
Government of India Planning Commission
Keywords: System & Constraints; Commodities Existing; Supply of Essential; Development of Services; Works in the North Eastern Region; Union Territories; Public Distribution System; Nagaland; Tripura; Arunachal Pradesh